Structure of a permutable Munn semigroup of finite rank - Derech, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
A semigroup any two congruences of which commute as binary relations is called a permutable semigroup. We describe the structure of a permutable Munn semigroup of finite rank.